Annotated Checklist of Armenian Platypodinae and Scolytinae (Coleoptera: Curculionidae) - Karagyan, Gayane; Kalashian, Mark; Ghrejyan, Tigran; Mazmanyan, Meri; Petrov, Аlexander (Zootaxa, 2024)
The paper presents a checklist of the bark and ambrosia beetles (Curculionidae: Platypodinae and Scolytinae) of Armenia. The fauna is comprised of one Platypodinae and Scolytinae 73 species, among which four species, Lymantor coryli (Perris, 1855), Ips typographus (Linnaeus, 1758), Orthotomicus erosus (Wollaston, 1857) and Scolytus eichhoffi Reitter, 1895 are recorded for the country for the first time. Sixty one species records are also provided for Armenia which were not mentioned in recent Catalogues of Palaearcic Curculionoidea.